Factors that Mediate the Effect of Eco-Label on Green Purchase Behavior Generation Z of Green Cement Products in Indonesia - Putri Rahmi Mardius; Sulastri Sulastri; Muchsin Saggaf Shihab (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
First, this study aims to see Green Purchase Behavior of Gen-Z in Indonesia towards green cement. Second, the study measures the indirect effect of  Eco-Label variable on the Green Purchase Behavior of Gen Z in Indonesia.Third this study measures the direct effect of the Perceived Customer Effectiveness (PCE), Product Attribute (PA), and Environmental Concern (EC) variables on the Green Purchase Behavior of Gen-Z in Indonesia.Fourth this study  also measure the ability of the PCE, Product Attribute, and Environmental Concern variables to mediate the Eco-label variable on Green Purchase Behavior.This study used an online questionnaire to conduct an empirical study by collecting and analyzing 411 samples using structural equation modeling (SEM).The findings in this study show that Eco-label has an indirect influence on Green Purchase Behavior Gen-Z in Indonesia, Eco-label also has a positive and significant influence on Environmental Concern (EC), Product Attribute (PA), and Perceived Customer Effectiveness (PCE) variables. These three variables are also able to significantly mediate the Eco label variable on Gen-Z’s Green Purchase Behavior (GPB) in Indonesia. The results of this study are expected to be able toserve as a guide for viewing dimensions” of the existing factors that most influence green purchasing behavior in generation Z”so as to increase sales of green products. The results of this study can also be used by policy makers in the field of marketing strategies for environmentally green products towards increasing the use of Eco-labels on their products and selecting suitable approaches to target Gen-Z in Indonesia through product attributes, environmental concerns, and Perceived Customer Effectiveness (PCE). What is new from this research in the observation of the Green Purchase Behavior of Gen Z in Indonesia, and also of green cement products as objects in this study.